Meilensteine der Entwicklung des Kapitalmarktes in Deutschland und der Kapitalmarkttheorie vom Ende der 1970er- bis zum Beginn der 1990er-Jahre - Bernd Rudolph (IBF - Institut für Bank- und Finanzgeschichte, 2017)
– This paper is a slightly revised version of a presentation that was given at the celebration of the Center for Finan-cial Studies at Goethe University Frankfurt on the occa-sion of the 80th birthday of Dr. Rolf-E. Breuer on Novem-ber 30, 2017. It illuminates the development of the ex-change environment and the exploration of the events in capital markets from the end of the 1970s to the begin-ning of the 1990s, that is the period in which Breuer had already made a name for himself as director of the ex-change department at Deutsche Bank, before he was ap-pointed to the Management Board of Deutsche Bank in 1985, and took over the chair of the Supervisory Board at Deutsche Börse in 1993. During this period Breuer made decisive contributions to the development of an efficient German capital market; he was the catalyst and driver of the emergence of an exchange environment.
Keywords: N24; O16; 330